Membangun Dusun Tuing dari Sektor Perikanan, Pariwisata, dan Pertanian - Eni Karsiningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2014)
Tuing Hamlet, Mapur Village, Riau Silip Sub-district, Bangka Regency is one of the underdeveloped hamlets in Bangka Regency. The main factor causing its underdevelopment is the very poor road access. However, Tuing Hamlet has beautiful tourism potential, unexplored fisheries and agriculture that still need to be developed. So that approaches need to be taken to improve and develop these sectors such as making fishing aids, providing GPS assistance, structuring the hamlet, conducting socialization with the local government, forming farmer groups, making vegetable demonstration plots and verticulture, providing super native chicken seeds and rubber seeds, socializing land ownership status laws, and making road paving RAB. Most of these service activities in Tuing Hamlet were successfully carried out so that the community could make squid FADs and fish FADs and knew the fishing points using GPS, knew the demonstration plot and verticulture methods and were able to breed super native chickens. Therefore, in order for Tuing Hamlet to get out of the shackles of underdevelopment, the local government should immediately pave the road based on the RAB that has been made, conduct socialization of Regional Regulation No. 1 of 2013, and collaborate with Universitas Bangka Belitung to make a master plan for tourism development in Tuing Hamlet.